Modification and Application of Dietary Fiber in Foods - Yue-yue Yang; Sen Ma; Xiao-xi Wang; Xue-ling Zheng (Journal of Chemistry)
Dietary fiber plays an important role in human health. The modification and application of dietary fiber in foods is reviewed with respect to definition and classification and methods for measurement, extraction, and modification of dietary fiber. The supplementation of dietary fiber for flour, meat, and dairy products is also reviewed. Finally, the benefits and risks of increasing consumption of dietary fiber are discussed.